Fermentation Production of Ganoderma lucidum by Bacillus subtilis Ameliorated Ceftriaxone-induced Intestinal Dysbiosis and Improved Intestinal Mucosal Barrier Function in Mice - Liu He; Fan Qing-Jie; Liu Yin-Hui; Li Ming; Yuan Jie-Li (KeAi Communications Co., Ltd., 2020)
Objective: This study aimed to develop a type of Ganoderma lucidum (G. lucidum)-probiotic fermentation broth that can effectively improve the intestinal mucosal barrier function of mice with ceftriaxone-induced intestinal dysbiosis. Methods: By means of absorbance of optical density (OD) value and phenol-concentrated sulfuric acid measurement of polysaccharide content, the probiotic species can grow on the medium of G. lucidum were screened out, and the concentration of the medium of G. lucidum was determined, and the fermentation broth was prepared for subsequent experiments. Thirty-two SPF grade male BALB/c mice were randomly divided into four groups (eight mice in each group), namely control group (CON), intestinal mucosal barrier damage model group (CS), fermentation broth intervention group (FT) and G. lucidum medium intervention group (GL), respectively. The intestinal dysregulation model was induced by intra-gastric administration of 0.2 mL ceftriaxone sodium (twice a day for seven consecutive days). From day 8, the FT group and GL group were gavage with 0.2 mL fermentation broth and G. lucidum medium, respectively. On day 15, all mice were sacrificed. To draw the weight curve and measure the cecal index; pathological examination of colon tissues with HE staining; serum levels of LPS, IL-10, TNF and IL-6 were detected by ELISA. Flow cytometry was used to analyze the changes of CD3 + T cells, CD4 + T cells, CD8 + T cells and macro- phages in spleen. 16S rRNA sequencing was performed to detect the intestinal microbiota structure of mice. Results: Bacillus subtilis can decompose and utilize G. lucidum fruiting body medium, and the suitable concentration of G. lucidum fruiting body medium is 33.2 mg/mL. The effect of Bacillus subtilis-G. lucidum fermentation broth on the damage of intestinal mucosal barrier caused by ceftriaxone sodium was reduced, the body weight of mice recovered and colon swellingimproved, colon histopathological injury was alleviated, inflammatory cell infiltration was alleviated, serum IL-10 increased significantly, LPS 、 TNF-α and IL-6 decreased significantly compared with model group, and the proportion of T cells and intestinal dysbiosis was improved. Conclusions: The experimental results suggest that Bacillus subtilis-G. lucidum fermentation broth can effectively improve the intestinal barrier function damage, immune dysfunction and intestinal dysbiosis caused by antibiotic overdose, and has a certain regulatory effect on intestinal mucosal barrier function.